Effect of Specific Yoga Protocol on Stress and Academic Performance in Adolescents - Priyanka; Sharma, Sunil; Kaushik, Naveen; Niharika; Choudhary, Ansh; Kaushik, Anuj (International Research Journal of Ayurveda & Yoga, 2024)
Background: This study investigates the impact of a structured Yoga protocol on perceived stress and academic performance among adolescents. Adolescence is a pivotal developmental stage often accompanied by heightened stress and academic pressures, which can adversely affect mental and physical health. Existing literature indicates that Yoga can effectively reduce stress and enhance cognitive functioning, making it a potential intervention in educational settings. Aim: The study aimed to evaluate the effectiveness of a specific Yoga protocol on stress management and academic performance in adolescents. Materials: A total of 70 participants from H.N. Model Senior Secondary School in Sanga, Bhiwani, were recruited for the study. Intervention: Participants were divided into an experimental group practicing a specific Yoga protocol (Yogāsana, Prāṇāyāma, and meditation) and a control group engaging in non-specific physical activities. Utilizing a pre-test and post-test control group design, the study assessed perceived stress using the perceived stress questionnaire and academic performance through the Academic Performance Rating Scale. Results: Results showed that the experimental group experienced a significant reduction in perceived stress, with pre-test mean values decreasing from 0.645 to 0.493, compared to a minor reduction in the control group from 0.617 to 0.550. Similarly, academic performance improved markedly in the experimental group, whose mean scores increased from 2.829 to 3.351, while the control group saw a smaller increase from 2.914 to 3.117. Conclusion: The findings suggest a strong correlation between the Yoga intervention and enhanced stress management and academic performance. This underscores the potential of incorporating Yoga into school curricula as an effective strategy for promoting holistic development among adolescents. By fostering emotional regulation and cognitive clarity, Yoga may contribute to improved learning environments and overall student well-being, warranting further exploration and implementation in educational settings.